Chinese livestock farms struggle under COVID-19 restrictions - Zhang, Xiaobo (International Food Policy Research Institute, 2020)
After the COVID-19 outbreak began in December in Hubei Province, many Chinese villages were locked down to control the spread of the disease. As the epidemic has eased, China has only begun to lift some restrictions. The lockdowns have had a significant — and still not well-understood — impact on the agriculture sector. The effective supply of agricultural products forms the foundation for a stable, functioning economy and safeguards people’s livelihoods. Thus, keeping agricultural enterprises running is an indispensable economic component in the ongoing battle against the epidemic — yet discussions of the outbreak have thus far devoted very little attention to the challenges they face.